Etching reaction of carbon quantum dot-functionalized MnO2 nanosheets with an enzymatic product for photoelectrochemical immunoassay of alpha-fetoprotein. (17th June 2022) - Lin, Junshan; Liu, Guozhong; Qiu, Zhixin; Huang, Lihong; Weng, Shangeng
Abstract : An etching reaction-based photoelectrochemical (PEC) immunoassay was developed to monitor alpha-fetoprotein (AFP) by coupling with the enzymatic product toward the dissolution of MnO2 nanosheets. Abstract : An etching reaction-based photoelectrochemical (PEC) immunoassay was developed to monitor alpha-fetoprotein (AFP) by coupling with the enzymatic product toward the dissolution of MnO2 nanosheets. Firstly, carbon quantum dot-functionalized MnO2 nanosheets (CQDs–MnO2 ) synthesized by the wet-chemistry method were modified onto a screen-printed carbon electrode (SPCE). Thereafter, monoclonal anti-AFP capture antibodies were covalently conjugated onto the CQDs–MnO2 photoactive materials via carbodiimide coupling. Polyclonal anti-AFP antibodies labeled with alkaline phosphatase (ALP) were used as the detection antibody for the development of a sandwiched immunoreaction mode. On subsequent addition of ascorbic acid 2-phosphate, the labeled ALP hydrolyzed it into ascorbic acid and phosphate. The produced ascorbic acid reduced MnO2 nanosheets to Mn 2+ ions, thereby resulting in the dissolution of the nanosheets. The functionalized CQDs were released from the nanosheets, accompanied by decreasing photocurrent. Under optimum conditions, the photocurrent of the CQDs–MnO2 -based PEC immunosensing platform decreased linearly with increasing AFP concentration in the range from 0.01 to 100 ng mL −1, and the limit of detection was 9.3 pg mL −1 . The precision of this system (expressed as RSD) was 13.7%. The accuracy was evaluated by analyzing human serum samples containing target AFP, and the results were in good accordance with those obtained by the established human AFP ELISA method.